Trastuzumab in combination with 5-fluorouracil, leucovorin, oxaliplatin and docetaxel as perioperative treatment for patients with human epidermal growth factor receptor 2-positive locally advanced esophagogastric adenocarcinoma: a phase II trial of the Arbeitsgemeinschaft Internistische Onkologie Gastric Cancer Study Group - Hofheinz, Ralf-Dieter; Hegewisch-Becker, Susanne; Kunzmann, Volker; Thuss-Patience, Peter; Fuchs, Martin; Homann, Nils; Graeven, Ullrich; Schulte, Nadine; Merx, Kirsten; Pohl, Michael; Held, Swantje; Keller, Ralph; et al. (International journal of cancer, 2021)
Perioperative chemotherapy with 5-fluorouracil, leucovorin, oxaliplatin and docetaxel (FLOT) is a mainstay in the treatment of esophagogastric adenocarcinomas (EGA). Trastuzumab improved survival when added to chemotherapy in patients with HER-2-positive metastatic EGA. We investigated the combination of trastuzumab and FLOT as perioperative treatment in patients with locally advanced EGA. A multicenter phase II study evaluated the efficacy and toxicity of perioperative FLOT (24-hours 5-FU 2600 mg/m2, leucovorin 200 mg/m2, oxaliplatin 85 mg/mg2, docetaxel 50 mg/m2, trastuzumab 6 mg/kg then 4 mg/kg d1, repeated d15 for four cycles preoperatively and postoperatively followed by 9 cycles of trastuzumab monotherapy) in patients with HER-2 positive EGA. Patients had ≥cT2, any N, M0 EGA. The primary endpoint was the rate of centrally assessed pathological complete response (pCR). Secondary endpoints comprised disease-free (DFS) and overall survival (OS), R0 resection rate, toxicity and surgical morbidity. Fifty-six evaluable patients (median age 62 years) were included; n = 40 had tumors originating from the esophagogastric junction; T stage was (cT2/3/4/unknown): 4/42/8/2; n = 50 patients had cN+ disease. Main adverse events grades 3-4: leukopenia (17.9%), neutropenia (46.6%) and diarrhea (17.0%). All patients underwent tumor resections. R0 resection rate was 92.9%. Eight patients had anastomotic leakage. One postoperative death occurred. pCR was found in 12 patients (21.4%) and a further n = 14 patients (25.0%) had near complete response. Median DFS was 42.5 months and the 3-year OS rate was 82.1%. The primary endpoint of achieving a pCR >20% was reached. No unexpected safety issues were observed. Survival data are promising.